Huge aspergilloma developed within a zone of scleroderma-related pulmonary fibrosis - Rakotoson, J L; Vololontiana, H M D; Raherison, R E; Andrianasolo, R L; Rakotomizao, J R; Rakotoharivelo, H; Rajaoarifetra, J; Randria, M J D; Rapelanoro, R F; Andrianarisoa, A C F; Rajaona, H R (Revue de pneumologie clinique, 2012)
In pulmonary aspergilloma, Aspergillus colonizes and proliferates as a saprophyte in deterged cavities deprived of local defense. Although pulmonary tuberculosis constitutes the one well-know predisposing factor, other causes can create favorable conditions. We describe a first published case of a huge aspergilloma which developed within a zone of pulmonary fibrosis secondary to systemic scleroderma. The patient was a 58-year-old woman in poor general health who experienced repeated episodes of hemoptysis and dyspnea. Physical examination disclosed sclerodactyly, generalized cutaneous sclerosis and Raynaud's phenomenon. There was no clinical history of pulmonary tuberculosis or bronchectasis. Aspergillosis serology was positive. Broncho-alveolar liquid was positive for Aspergillus fumigatus at direct examination and after culture. Immunological assessment confirmed scleroderma. The chest computed tomography scan showed a huge oblong-shaped opacity in the upper left lobe which had developed within a zone of pulmonary fibrosis. Medical management was instituted. The clinical course was marked by repeating hemoptysis and the stability of pulmonary lesions after two years. Management of scleroderma-related pulmonary aspergiloma remains difficult and complicated. Prognosis depends on the course of both conditions, scleroderma and aspergillosis.